Histological Findings Upon Patients Undergoing Revision Surgery after AMIC of the Talus. Issue 1 (January 2022) - Krause, Fabian; Anwander, Helen; Schaefer, Birgit
Category: Ankle Arthritis Introduction/Purpose: Failure after AMIC (autologous matrix-induced chondroplasty) of the talus is relatively rare and ranges between 2-6%. The purpose of the study was to analyze the histologic quality of the repair cartilage and potentially identify the mode of failure in 3 patients that underwent revision surgery after primary AMIC procedures. Methods: Out of 48 patients treated with AMIC for OLT between 2012 and 2018 at our institution, three patients (6.2%, average age 27.3 years) required revision surgery for various reasons. During revision, repair cartilage was evaluated about integration with the surrounding healthy cartilage and firmness, and specimen were taken for histologic assessment. Results: Only one patient that had, next to revision AMIC, a lateral ligament reconstruction for a secondary supination sprain, improved clinically after revision surgery (patient no.3). Despite repair SMOT (no.1) or deltoid ligament repair (no.1), the two other patients did not benefit from revision. Supposed reasons for ongoing symptoms were progressive posttraumatic arthritis (no.1 and 2) and neuropathic pain (no.2). Three types of soft connective tissues could be identified: (i) non-vascularized fibrocartilaginous tissue (patient no. 1-3), (ii) fibrous tissue (patient no. 1 and 2), and (iii) hyaline like cartilage (patient no. 3). Conclusion: Overall, data support the theory that patients with hyaline or hyaline-like repair cartilage tend to better clinical outcome over time. However, the growth of hyaline or hyaline-like repair cartilage appears to require ligamentous stability, neutral or even offloading hindfoot alignment, and absence of arthritis.